Perceptions of undergraduate nursing students toward providing care to COVID-19 patients - Faizi, Fakhrudin; Moradian, Seyed Tayeb (Frontiers in Public Health, 2022)
Background Undergraduate nursing students were inevitably recruited to provide care in response to overloaded hospitals with COVID-19 patients. The placement was potentially a stressful event and we aimed to understand the students' perception of direct nursing care during the pandemic. Methods This qualitative content analysis study carried out in 2020 (May-June) in Tehran, I.R. Iran. Using explanatory questions, we interviewed 15 undergraduate nursing students who provided direct care for at least 2 months to patients hospitalized with COVID-19 in the beginning of the pandemic to obtain their deep experiences. We applied the MAXQDA 10 to extract codes, used the qualitative content analysis method for investigation, and then applied the Lincoln and Guba criteria for rigor and trustworthiness. The study was approved by the National Committee for Ethics in Biomedical Research (IR.BMSU.REC.1399.070. available at: https://ethics.research.ac.ir). Results Four hundred and 54 codes were identified, which were then sorted into 12 categories underlying four main themes of “hard and unpredictable,” “posttraumatic growth,” “on the path to self-determination,” and “commitment.” Conclusion Even though the undergraduate nursing students experienced some stress in the beginning, with close support, their caregiving skills improved and they were able to meet the national healthcare needs. More studies are needed to confirm our findings regarding the experiences of the nursing students in combating COVID-19.